Development and Implementation of a Capstone Objective Structured Clinical Examination in Nurse Practitioner and Nurse-Midwifery Programs. Issue 6 (November 2016) - Benbenek, Mary; Dierich, Mary; Wyman, Jean; Avery, Melissa; Juve, Catherine; Miller, Jane
Abstract : Determining when advanced practice registered nurse students are safe and competent for beginning-level practice is challenging. This article describes the development and testing of a capstone objective structured clinical examination designed to evaluate the practice readiness of students enrolled in the family, adult-gerontology, women's health nurse practitioner, and nurse-midwifery tracks. Lessons learned from this process and how they were used to enhance the curricula are discussed.